2011
DOI: 10.1258/ar.2010.090482
|View full text |Cite
|
Sign up to set email alerts
|

Pathological 99mTc-sestamibi myocardial perfusion scintigraphy is independently associated with emerging cardiac events in elderly patients with known or suspected coronary artery disease

Abstract: Pathological MPS is independently associated with emerging cardiac events predicting a significantly lower incidence of cardiac event-free survival in patients aged ≥70 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Also, higher SSS was linked to lower event-free survival rate [18]. Moreover, Bucerius et al had reported that higher SSS is independently associated with cardiac events and lower incidence of cardiac event-free survival in the elderly [19]. However, in patients with severe left ventricular (LV) systolic dysfunction (LV ejection fraction ≤35%), Gimelli et al showed that SSS is less predictive of outcome compared to patients with better preserved systolic dysfunction [20].…”
Section: Discussionmentioning
confidence: 99%
“…Also, higher SSS was linked to lower event-free survival rate [18]. Moreover, Bucerius et al had reported that higher SSS is independently associated with cardiac events and lower incidence of cardiac event-free survival in the elderly [19]. However, in patients with severe left ventricular (LV) systolic dysfunction (LV ejection fraction ≤35%), Gimelli et al showed that SSS is less predictive of outcome compared to patients with better preserved systolic dysfunction [20].…”
Section: Discussionmentioning
confidence: 99%